2007
DOI: 10.1094/cchem-84-1-0048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gluten Proteins and Drying Temperature on the Cooking Quality of Durum Wheat Pasta

Abstract: It is well known that gluten plays a major role in determining cooking quality in durum wheat pasta. This work is an attempt to systematically elucidate the role of gluten quantity and nature in determining cooking quality as a function of the drying cycle used in the manufacturing process. Gluten and starch were fractionated from two durum wheat cultivars possessing good and poor gluten quality. Either of them were then added back to the original base semolina to alter its protein content and to produce two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 23 publications
14
84
0
1
Order By: Relevance
“…Petitot et al (2009) also reported increased hardness in pasta dried at high temperatures. Similar results were obtained by Cubadda, Carcea, Marconi, and Trivisonno (2007), who investigated the influence of drying temperature on the cooking quality of durum wheat pasta. Figure 2 shows the results for pasta adhesiveness.…”
Section: Textural Propertiessupporting
confidence: 84%
“…Petitot et al (2009) also reported increased hardness in pasta dried at high temperatures. Similar results were obtained by Cubadda, Carcea, Marconi, and Trivisonno (2007), who investigated the influence of drying temperature on the cooking quality of durum wheat pasta. Figure 2 shows the results for pasta adhesiveness.…”
Section: Textural Propertiessupporting
confidence: 84%
“…Drying is the end phase of pasta processing, and this can also influence the final cooking quality of the pasta (Cubadda et al 2007). Pasta yellowness is the result of concurrent chemical and physical factors.…”
Section: Pasta Processing Conditions That Affect the Yellow Pigment Dmentioning
confidence: 99%
“…Shorter cooking time was required for fresh SN (3.45 min) compared to CN (5.15 min). Investigations have shown that gluten content governs the optimum cooking time (Cubadda et al 2007; Fig. 5 Effect of wall materials on viability of L. plantarum during storage of freeze dried microcapsules at 4°C.…”
Section: Optimum Cooking Time and Solid Lossmentioning
confidence: 99%
“…Error bars represent standard deviation of means (n=3) Dipin et al 2012). Incorporation of probiotic microcapsules decrease the gluten level that allows the rapid gelatinization, and reduces the cooking time (Cubadda et al 2007). Choy et al (2013) reported that significant reduction in the cooking time for noodles containing buckwheat flour due to the physical disruption of the gluten matrix which in turn provided a path for rapid water absorption into noodle.…”
Section: Optimum Cooking Time and Solid Lossmentioning
confidence: 99%
See 1 more Smart Citation